Executive coaching explained: the beginnings of a contingency approach. Issue 9 (9th September 2020) - Offstein, Evan H.; Dufresne, Ronald L.; Childers Jr, John S.
Abstract : Purpose: In this paper, we problematize the prevailing assumptions in the executive coaching literature that effective coaching is deliberative, trust-based and relational in nature, thereby requiring significant time investment before the focal leader might realize enacted benefits from the coaching. Contrary to these prevailing assumptions, we propose five contingencies wherein a more direct, performance-first approach to coaching may be more effective. Design/methodology/approach: This conceptual paper reviews relevant literature to develop testable propositions regarding directive coaching contingencies. Findings: We develop propositions that argue executive coaches will need to employ a more directive, urgent and accountable coaching relationship when the executive's career is in jeopardy, the organization is in distress, if the leader needs to signal legitimacy, if the coaching occurs within the boundaries of a high reliability organization or if the coach is working with an executive who has interim status. Originality/value: This paper intends to advance the theory and practice of executive coaching by challenging executive coaching orthodoxy regarding the need for a deliberative, relational approach to coaching. Future research should broaden this theorizing and empirically test our propositions.